2021
DOI: 10.3390/molecules26051276
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength and Film Thickness of a Naturally Antimicrobial Modified Dental Luting Cement

Abstract: Although several natural plants and mixtures have been known and used over the centuries for their antibacterial activity, few have been thoroughly explored in the field of dentistry. Thus, the aim of this study was to enhance the antimicrobial activity of a conventional glass ionomer cement (GIC) with natural plant extracts. The effect of this alteration on the bond strength and film thickness of glass ionomer cement was evaluated and related to an 0.5% chlorohexidine modified GIC. Olive leaves (Olea europaea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The particles, content, size, and shape of the filler can be considered factors that affect film thickness [36]. A thicker film thickness of the adhesive can affect the decrease in bonding strength, and previous studies have shown that the thinner the film thickness, the less load is removed during bracket debonding [37,38]. According to the TEM image analysis results, the particle sizes of ZnO and HNTs are 1-10 nm and 1 µm, respectively, indicating that HNTs are relatively larger than ZnO.…”
Section: Discussionmentioning
confidence: 99%
“…The particles, content, size, and shape of the filler can be considered factors that affect film thickness [36]. A thicker film thickness of the adhesive can affect the decrease in bonding strength, and previous studies have shown that the thinner the film thickness, the less load is removed during bracket debonding [37,38]. According to the TEM image analysis results, the particle sizes of ZnO and HNTs are 1-10 nm and 1 µm, respectively, indicating that HNTs are relatively larger than ZnO.…”
Section: Discussionmentioning
confidence: 99%
“…During the bonding of the restoration, reducing the film thickness can also decrease the marginal discrepancies, which are essential for the complete seating and adaptation of the restoration. Furthermore, a thin film thickness reduces cement dissolution, intra-restoration plaque accumulation, and the progression of periodontal disease 43 . In the present study, RMC-I presented the most favorable thickness, with the incorporation of ZD being least affected by the ZD concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The FT and proper adaption of the restoration are both directly impacted by the consistency of the luting agent. More time and force are required for proper restoration seating when using a luting agent with a high viscosity [48].…”
Section: Discussionmentioning
confidence: 99%